2009
DOI: 10.1242/jcs.054007
|View full text |Cite
|
Sign up to set email alerts
|

HSCARG inhibits activation of NF-κB by interacting with IκB kinase-β

Abstract: HSCARG is a recently identified human NADPH sensor. Our previous studies have shown that HSCARG can affect NO production and cell viability, but the signal pathway mediated by this protein is unknown. Here, we show that HSCARG is involved in the NF-B signaling pathway and find that HSCARG suppresses TNF-and IL1-induced NF-B activation in a dose-dependent manner. Co-immunoprecipitation and immunofluorescence analyses demonstrate that HSCARG interacts and colocalizes with IKK. HSCARG inhibits the phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…co-IP and western blot analyses were performed following procedures described previously (33). Briefly, HEK293T cells were transfected with the indicated plasmids.…”
Section: Methodsmentioning
confidence: 99%
“…co-IP and western blot analyses were performed following procedures described previously (33). Briefly, HEK293T cells were transfected with the indicated plasmids.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we demonstrated that HSCARG interacts with IKK β and suppresses its phosphorylation by promoting the interaction between PP2A and IKK β , 32 which provided one of the possible mechanisms to explain how HSCARG inhibits IKK β phosphorylation and NF- κ B activity. To further investigate which protein was the direct interaction partner of HSCARG, we carried out in vitro pull-down assays between HSCARG and NEMO or IKK β .…”
Section: Discussionmentioning
confidence: 95%
“…HSCARG is a newly identified NF- κ B inhibitor. 32 Here we elucidated the detailed mechanism in which HSCARG inhibits NF- κ B activity. HSCARG interacts with USP7 and inhibits the polyubiquitination of NEMO, which decreases proteasomal degradation of I κ B α and further inhibits NF- κ B activity (Figure 6).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…HSCARG (also named NmrA-like family domain-containing protein 1 or NMRAL1) is a newly-identified NADPH sensor and negative regulator of NF-κB [29]. It contains a Rossmann-fold in the N terminus and forms an asymmetrical dimer with only one subunit occupied by one NADP molecule [30].…”
Section: Introductionmentioning
confidence: 99%